2021
DOI: 10.1038/s41598-021-87138-6
|View full text |Cite|
|
Sign up to set email alerts
|

Distinguishing chronic low back pain in young adults with mild to moderate pain and disability using trunk compliance

Abstract: Chronic low back pain (cLBP) rates among younger individuals are rising. Although pain and disability are often less severe, underlying changes in trunk behavior may be responsible for recurrence. We examine the biomarker capacity of a simple Trunk Compliance Index (TCI) to distinguish individuals with and without cLBP. A random subset (n = 49) of the RELIEF RCT were matched to healthy controls for sex, age, height and weight. We measured TCI (as displacement/ weight-normalized perturbation force) using anthro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…The use of a 5-choice Likert scale was also made to reflect the school grading system, which participants were familiar with. Based on the risk-intensity association for back pain proposed in previous studies [ 27 , 28 , 29 ], and in accordance with Joergensen et el. [ 30 ], based on their responses participants were grouped into three main categories: no back pain (NBP: students who stated not to suffer from back pain; score = 1); mild-to-moderate back pain (MBP: participants with low to null health risk; scores = 2–3); and severe back pain (SBP: youth whose back pain may imply higher health risk; scores > 3).…”
Section: Methodssupporting
confidence: 68%
“…The use of a 5-choice Likert scale was also made to reflect the school grading system, which participants were familiar with. Based on the risk-intensity association for back pain proposed in previous studies [ 27 , 28 , 29 ], and in accordance with Joergensen et el. [ 30 ], based on their responses participants were grouped into three main categories: no back pain (NBP: students who stated not to suffer from back pain; score = 1); mild-to-moderate back pain (MBP: participants with low to null health risk; scores = 2–3); and severe back pain (SBP: youth whose back pain may imply higher health risk; scores > 3).…”
Section: Methodssupporting
confidence: 68%
“…When it comes to the human body, stiffness can be explained in a wide range of contexts, from a single muscle fiber to the whole body. Muscle stiffness is the muscle’s ability to maintain its initial structure against external forces to prevent deformities [ 17 ]. Several studies have investigated the alterations of muscle stiffness due to aging; however, the results are conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that the lifetime prevalence of LBP is as high as 84% and known to cause massive individual and economic burdens in industrialized nations such as Korea [ 6 , 7 , 8 ]. In addition, numerous studies have shown that adolescent LBP is a strong predictor for chronic LBP problems in adulthood [ 6 , 9 , 10 , 11 ]. Most cases of LBP are due to herniated discs, 98% of which occur in the L4–5 disc [ 2 ].…”
Section: Introductionmentioning
confidence: 99%